Desain Grafis dalam Perpustakaan Indonesia: Kesiapan, Peran dan Harapan Pustakawan - Destrianto, Mochammad Riski (Nusantara Journal of Information and Library Studies (N-JILS), 2024)
This study employs a qualitative approach to explore the roles and readiness of librarians in graphic design in Indonesian libraries. Data were collected through an online survey with semi-open questions to 92 respondents, and then analyzed to identify emerging themes and patterns. The results indicate that the majority of librarians are involved in graphic design due to a lack of human resources and personal initiative, with a variety of design products produced including social media materials, posters, and infographics. Challenges faced by librarians include a lack of skills and training, as well as limited software and hardware. Based on these findings, it is recommended that support be provided in the form of courses and workshops, clear design templates and guidelines, adequate allocation of software and hardware, and sufficient time for librarians to delve into graphic design. It is hoped that these findings can serve as a reference for further development related to graphic design in Indonesian libraries. Keyword: Librarian, graphic design, indonesia library, qualitative research.   ABSTRAK Penelitian ini menggunakan pendekatan kualitatif untuk menggali peran dan kesiapan pustakawan dalam desain grafis di perpustakaan Indonesia. Data dikumpulkan melalui survei daring dengan pertanyaan semi-open question kepada 92 responden, kemudian dianalisis untuk mengidentifikasi tema dan pola yang muncul. Hasil menunjukkan mayoritas pustakawan terlibat dalam desain grafis karena kekurangan sumber daya manusia dan inisiatif pribadi, dengan beragam produk desain yang dihasilkan termasuk materi untuk media sosial, poster, dan infografis. Kendala yang dihadapi pustakawan meliputi kurangnya keterampilan dan pelatihan, serta keterbatasan perangkat lunak dan keras. Berdasarkan temuan ini, disarankan perlu adanya dukungan berupa kursus dan workshop, template dan panduan desain yang jelas, alokasi perangkat lunak dan keras yang memadai, serta waktu yang cukup bagi pustakawan untuk mendalami desain grafis. Temuan ini diharapkan dapat menjadi referensi untuk pengembangan lebih lanjut terkait desain grafis di perpustakaan Indonesia.